PENGEMBANGAN MEDIA VIDEO BERBASIS APLIKASI KINEMASTER PADA TEMA INDAHNYA KERAGAMAN NEGERIKU DI KELAS IV SD - Hanisah Hutasuhut (PGSD UMN Al-Washliyah, 2022)
This research was background by the media used by the teacher had not varied. This study aims to develop a video media based on the Kinemaster application with the theme of the beauty of my country's diversity in the fourth grade of elementary school. The research used research and development (R&D) with the borg and gall model which consists of five steps, namely; (1) design product, (2) collection data, (3) design product, (4) design validation, (5) design revision, to test the validity and feasibility of a developed media. The research was conducted in the fourth grade of SD Negeri 060925 Medan with the theme of the beauty of my country's diversity. The technique of collected data used a media expert questionnaire, a material expert questionnaire and a teacher. Validation of media was expert with an 82% eligibility percentage which was included in the